Natural Tooth Pontic and FRC splint Using Special Rigid Tray Technique (A Case Report) - Saied Mostafa Moazzami; Sanaz Alizadeh; Sara Sarvari (Mashhad University of Medical Sciences, 2015)
Making a conservative bridge using a natural tooth pontic with mobile teeth is complicated, time-consuming and sometimes impossible with the current techniques and materials. The aim of this paper is` to describe a new method using Special Rigid Tray Technique (SRTT) to deal with such difficult clinical cases.